The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1373/clinchem.2007.092312
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Liquid Microbead Arrays for the Screening of Newborns for Spinal Muscular Atrophy

Abstract: Background:Spinal muscular atrophy is a common neurodegenerative disorder that has recently been considered for inclusion in the next generation of newborn screening regimens. We sought to validate liquid microbead arrays for the identification of affected individuals by direct DNA analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…[43][44][45] Laboratory quality control X-ALD NBS materials are under development. 46 Research is also ongoing to develop laboratory methods and assess public perceptions for other conditions including Fragile-X, 47,48 spinal muscular atrophy (SMA), 49,50 Wilson's disease, 51 and guanidinoacetate methyltransferase (GAMT) deficiency. 52 With increasing interest in NBS, and the possibility of extracting DNA from residual dried blood spot (DBS) specimens, has come an increasing awareness of privacy issues, particularly since NBS in the U.S. is legally required and consent is usually not included as part of U.S. screening protocols.…”
Section: North Americamentioning
confidence: 99%
“…[43][44][45] Laboratory quality control X-ALD NBS materials are under development. 46 Research is also ongoing to develop laboratory methods and assess public perceptions for other conditions including Fragile-X, 47,48 spinal muscular atrophy (SMA), 49,50 Wilson's disease, 51 and guanidinoacetate methyltransferase (GAMT) deficiency. 52 With increasing interest in NBS, and the possibility of extracting DNA from residual dried blood spot (DBS) specimens, has come an increasing awareness of privacy issues, particularly since NBS in the U.S. is legally required and consent is usually not included as part of U.S. screening protocols.…”
Section: North Americamentioning
confidence: 99%
“…In 2007, Pyatt et al showed that it was possible to extract sufficient DNA from the standard NBS blood spots to effectively screen for SMA, with a sensitivity of 100% and a specificity of 99.5% (Pyatt, 2007). The sensitivity would be closer to 95-98% after accounting for the small percentage of affected people who do not have homozygous SMN1 deletions (Prior, 2010 (Prior, 2010).…”
Section: Nbs For Smamentioning
confidence: 99%
“…With its sizeable capacity for multiplexing, array technology has been touted as the application of choice for the first-tier analysis of DNA in newborn screening. 33,34 Using liquid microbead array for the detection of the homozygous SMN1 exon 7 deletion, Pyatt et al 35 demonstrated that newborn screening for SMA can be technically accomplished. In a series of blood spots, all 164 affected samples were correctly found to have the homozygous SMN1 deletion, whereas 157 unaffected samples were excluded.…”
Section: Newborn Screeningmentioning
confidence: 99%
“…In a series of blood spots, all 164 affected samples were correctly found to have the homozygous SMN1 deletion, whereas 157 unaffected samples were excluded. 35 There is a growing consensus that newborn screening can be extremely valuable for genetic conditions for which we do not have a specific effective treatment. A newborn screening program for SMA would not only allow patients to be enrolled in the clinical trials at the earliest time period but would enable patients to obtain proactive treatment earlier in the disease progression with regard to nutrition, physical therapy, and respiratory care.…”
Section: Newborn Screeningmentioning
confidence: 99%